Normative Juridical Review of Legal Protection of Underage Child Laborers - Rizki Gusti Perdana (UM Purwokerto Press, 2023)
Exploitation of child labor still occurs in Indonesia. Poverty and weak legal protection of children is one contributing factor. Therefore this paper aims to examine the factors that cause the emergence of child labor, child rights and legal protection for child workers, and prevention of child labor in Indonesia. The results of this study indicate that the occurrence of child labor is influenced by various social factors such as poverty and economic. Protection of child labor has been arranged in the formulation of laws and International Conventions ratified by Indonesia. Various efforts have been made to overcome the problem of child labor, but the government's effort is not maximized as expected.